2021
DOI: 10.1051/e3sconf/202131901029
|View full text |Cite
|
Sign up to set email alerts
|

Academic stress and burnout among primary school trainee teachers in the Rabat-Sale-Kenitra region

Abstract: During the training phase, the trainee teacher seems to be more and more confronted with discomfort and stress, due to the accumulation of demands and obligations. Many of them are mostly unable to take it any longer, which makes them vulnerable to the burnout risk. This research aims to study the academic burnout of trainee teachers at the “Centre Régional des Métiers de l’Education et de la Formation “(CRMEF) of the Rabat-Sale-Kenitra region during 2019/2020. Four hundred and fifty trainee teachers responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…This dimension is based on the feeling of self-efficacy, teachers with low academic efficiency generally feel overwhelmed by the demands of training and feel pressure and stress. [ 21 ] This finding confirmed previous related studies on academic burnout,[ 22 23 24 25 ] which concluded that effective students reported lower levels of burnout than their less effective colleagues. It is clear, therefore, that students in our sample who progress to higher levels of education (Master's, PhD) have a higher level of AE [ Table 3 ].…”
Section: Discussionsupporting
confidence: 85%
“…This dimension is based on the feeling of self-efficacy, teachers with low academic efficiency generally feel overwhelmed by the demands of training and feel pressure and stress. [ 21 ] This finding confirmed previous related studies on academic burnout,[ 22 23 24 25 ] which concluded that effective students reported lower levels of burnout than their less effective colleagues. It is clear, therefore, that students in our sample who progress to higher levels of education (Master's, PhD) have a higher level of AE [ Table 3 ].…”
Section: Discussionsupporting
confidence: 85%
“…Internal consistency of the three dimensions (EE, CY, and AE) indicated acceptable psychometric quality. [ 27 28 ]…”
Section: Discussionmentioning
confidence: 99%